Teacher Form of Psychological Pathology for Adoloscents: Development of Preliminary Version and Psychomentric Evaluation - Akbari Zardkhaneh , Saeed; Sajjadi anari , Seyed Saeid; Mansurkiaie , Nader; Zanganeh , Alimohammad; Jallalat-Danesh , Mohsen (Journal of Assessment and Research in Applied Counseling (JARAC), 2022)
Background and Aim: Emotional-behavioral disorders in Adoloscents are prevalent, which cause many problems for family and adoloscents themselves and are accompayning with social negative consequences. Present study aims to develop a scale of psychological pathology for adoloscents-teacher form.  Methods: An initial item pool of 190 was generated and after first edition 119 items were selected to comprise the preliminary version of the scale. Population includes teachers of high school students in six states of Alborz, Eastern Azerbaijan, Sistan & Baluchestan, Fars & Khorasan Razavi. Sample includes about 370 teachers in each states which were randomly chosen from two cities in each states. Results: Factor analysis with generalized least squares method and equamax rotation was performed on the item responses and yielded a 6 factor solution which is consistent with the theoretical framework. Reliability coefficients of subscales ranged between 0.81 (Anxiety) and 0.95 (Academic Achievement Deficit and Self-regulation). Evaluation of correlation coefficients between items and subscales illustrated those coefficients to vary between 0.35 (item 26) and 0.84 (item 59). Conclusion: In general, results showed that regarding good psychometric properties of mental health scale for adoloscents-teacher form, it can be used for assessing behavioral and emotional problems in educational, therapeutic, and clinical facilities in Iran population